Å snakke om det som ikke skal nevnes! – Om bruken av samtaleverktøyet «LeVel» overfor unge som har utvist skadelig seksuell adferd. - Amundsen, Marie-Lisbet; Garmannslund, Per E. (Nordisk Tidsskrift for Kriminalvidenskab, 2023)
Abstract This article examines the use of a conversation tool called »LeVel«, which employees of the Norwegian Probation Service use when talking with young boys who are serving a youth sentence. Two focus group interviews have been carried out among employees. Interview data were analyzed using thematic analysis based on two questions: to what extent do staff members in the probation service feel that a conversation tool can be of support when conducting conversations with boys who have committed sexual abuse; and what importance do employees think the conversation tool has for conversations with these young people? The informants are generally positive about the conversation tool, but they point out that the fact that conversations are not based on voluntary participation is a challenge. Furthermore, the tool is not adapted to users with language difficulties, neurological diagnoses or cognitive difficulties. The informants also indicate that the time frames available for conversations vary greatly, which means that one is in danger of having to finish conversations earlier than desired.